P106 Lung Clearance Index is a Repeatable Test of Lung Function and Superior Predictor of CT Scan Abnormalities in Bronchiectasis. (14th November 2013) - Rowan, S; Bradley, J; Bradbury, I; Lawson, J; Lynch, T; O'Neill, K; Ennis, M; Elborn, JS
Abstract : Introduction: In cystic fibrosis, lung clearance index (LCI) is a sensitive predictor of CT scan determined lung pathology. In bronchiectasis (BE) there is a need for improved markers of lung function to gauge disease severity and response to interventions in clinical trials. Aims: To assess if LCI is a repeatable and superior predictor of CT scan abnormalities compared with FEV1 in BE. Methods: 60 patients with stable BE were recruited. LCI (using SF6 multiple breath washout), spirometry and CT scores were collected. Health related quality of life (HRQoL) was measured using the St. George's Respiratory Questionnaire. A separate group of 30 BE patients were recruited and LCI, spirometry and HRQoL were assessed when clinically stable on 2 occasions, 2 weeks apart. Results: Mean (SD) age was 62 (10) years, FEV1 76.5 (18.9)% predicted, LCI 9.1 (2.0) and total CT score 14.1 (10.2)%. FEV1 negatively correlated with LCI (r = -0.51, p < 0.0001.) Across all CT score subscales, there was clear evidence of a relationship with LCI, with no or very weak evidence of any additional effect of FEV1 . The strongest correlations of subgroup CT scores with LCI were seen in), % parenchymal score (r = 0.56, p < 0.001), % mucus plugging (r = 0.49, p < 0.001), % total score (r = 0.55, p < 0.001)% bronchiectasis (r = 0.41, p < 0.01. There was no association for either FEV1 or LCI with% airway thickening and for % bronchiectasis score and FEV1 . There were no significant associations between LCI or FEV1 and HRQoL. The inter-visit ICC for LCI was 0.94 (95% CI 0.89 to 0.97, p < 0.001). Conclusions: LCI is a valid and repeatable test of lung function in BE. It is a superior predictor of lung function than FEV1 in the detection of abnormalities demonstrated on CT scan. LCI is a useful test in patients with early lung disease or those with preserved spirometric scores. LCI also has the potential to be an alternative outcome measure to spirometry in clinical trials.